Biofilm formation and detection of A/D genes in MRSA (Methicillin-Resistant Staphylococcus aureus) and MSSA (Methicillin-Sensitive Staphylococcus aureus) - Rini Purbowati (The East Java Biological Society, 2019)
MRSA (Methicillin-Resistant Staphylococcus aureus) arises due to excessive use of methicillin antibiotics and complications from all medical practices that have been carried out lately. The prevalence of MRSA tends to increase and its ability to form biofilms so that it has the potential to significantly increase mortality and morbidity. Biofilms are considered one of the microbial virulence factors. Biofilm formation in S. aureus is regulated by the expression of PIA which mediates attachment between cells to cells and is a product of the ABDC ica gene. This study aims to determine the ability of biofilm formation as one of the virulence factors in MRSA compared to MSSA (Methicillin-Sensitive Staphylococcus aureus) . its relationship to the presence of A and D ica genes as biofilm coding genes. Biofilm formation assay on MRSA and MSSA using the Microtiter Plate (MtP) method and the A/D gene detection assay performed by PCR method. The results showed that the incubation end value of Optical Density (OD) for MSSA1 (0.75), MSSA2 (0.46), MRSA1 (0.53) isolates according to the formula were interpreted as moderate biofilm producer. The conclusions of this study were all of the test isolates (MSSA1, MSSA2 and MRSA1) were able to form a biofilm. Distribution of ica A and ica D genes in MSSA 1 and MSSA 2 was varied while MRSA1 had the ica A and ica D genes.